A survey on acceptance and readiness to use robot teaching technology among primary school science teachers - Nagendra Rao, Laxmi; Ab Jalil, Habibah (Canadian Center of Science and Education, 2021)
Interest in educational robotics has grown in recent years, and many efforts have been undertaken across the globe to include robots into school instruction from kindergarten to high school, mostly in science and technology subjects. The current study is to determine teachers' technological acceptance and readiness to implement robotic technology in the teaching and learning process. A descriptive research design was employed which utilized a survey method. This survey was conducted among primary school teachers of Science, Mathematics, Design and Technology, and Information and Communication Technology (ICT) in Malaysia. According to the findings, teachers' acceptance of robot technology in the classroom is at a modest 3.77 (SD = 0.598) while the readiness score is 3.67 (SD = 0.611). The findings indicated that school teachers are only moderately prepared to employ robotic technology in classrooms. Respondents also argued that the high cost of robotic technology is a significant barrier to incorporate robotic technology into teaching and learning. The practicality of this paper is the provision of insights for exploring adoption possibilities and barriers in auguring robots into primary school classrooms. This indicates that the higher the level of teachers’ acceptance, the higher teachers’ readiness in robotic technology. Respondents argued that the high cost of robotic technology is a significant barrier to incorporating robotic technology into teaching and learning.